2015
DOI: 10.1002/pi.5041
|View full text |Cite
|
Sign up to set email alerts
|

Grafting design: a strategy to increase the performance of radiation‐grafted membranes

Abstract: The polymer design concept of short versus long side chains was successfully adapted to radiation-grafted membranes, the fabrication of which is an easy and up-scalable process. This concept was investigated by the generation of two model membranes based on polystyrene sulfonic acid-grafted ethylene-alt-tetrafluoroethylene, prepared using a low versus high irradiation dose. It was shown to be essential to adjust the grafting parameters of both systems to obtain two membranes with similar composition in through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…These PEMs were referred to as L‐PEM (low‐dose) and H‐PEM (high‐dose). To obtain the same through‐plane homogeneity, the grafting conditions were carefully chosen (see Through‐Plane Homogeneity Optimization, Supporting Information) . This homogeneity influences the performance of the system and also the scattering signal (see Correlation between Microstructure and Grafting Kinetics, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These PEMs were referred to as L‐PEM (low‐dose) and H‐PEM (high‐dose). To obtain the same through‐plane homogeneity, the grafting conditions were carefully chosen (see Through‐Plane Homogeneity Optimization, Supporting Information) . This homogeneity influences the performance of the system and also the scattering signal (see Correlation between Microstructure and Grafting Kinetics, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…However, it was recently shown that the irradiation dose has a clear impact on the performance when preparing PEMs based on a well‐known model system: sulfonated polystyrene grafted onto poly(ethylene‐ alt ‐tetrafluoroethylene), ETFE‐ g ‐PS(SA). Even though the PEMs had identical ion exchange capacity values, higher irradiation dose resulted in increased water sorption and proton conductivity, in particular at low relative humidity values …”
Section: Introductionmentioning
confidence: 99%
“…resistances and durabilities in fuel cells). 16 The synthesis and characterisation of BVPE is detailed in the ESI ‡ (the Raman spectrum is presented in Fig. 1).…”
Section: Rg-cems Made Using Bis(vinylphenyl)ethane (Bvpe) Crosslinkermentioning
confidence: 99%
“…6 Incomplete graing can lead to RG-IEMs with lower than ideal functionalisation, which are then too ionically resistive for application. Radiation-graing oen involves the graing-front mechanism, especially with thicker precursor lms: [6][7][8] this is where graing initiates on the surfaces of the precursor lms with the gradual penetration of the gras into the bulk of the lms (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…As radiation-graing involves the modication of solid polymer lms (up to 150 mm thickness in the literature), 1 it is essential to assess the uniformity of the monomer graing (and any subsequent functionalisation) throughout the core of the resulting RG-IEMs. 9 Techniques that have been used to study the uniformity of graing include Scanning Electron Microscopy coupled with Energy-Dispersive X-ray Spectroscopy (SEM-EDX) 8,10 and Raman spectro-microscopy. 6,9,11 Raman spectroscopy can achieve spectral resolutions down to ca.…”
Section: Introductionmentioning
confidence: 99%